A genomic approach to study down syndrome and cancer inverse comorbidity: untangling the chromosome 21 - Forés-Martos, Jaume; Cervera-Vidal, Raimundo; Chirivella, Enrique; Ramos-Jarero, Alberto; Climent, Joan (Frontiers in Physiology, 2015)
Down syndrome (DS), one of the most common birth defects and the most widespread genetic cause of intellectual disabilities, is caused by extra genetic material on chromosome 21 (HSA21). The increased genomic dosage of trisomy 21 is thought to be responsible for the distinct DS phenotypes, including an increased risk of developing some types of childhood leukemia and germ cell tumors. Patients with DS, however, have a strikingly lower incidence of many other solid tumors. We hypothesized that the third copy of genes located in HSA21 may have an important role on the protective effect that DS patients show against most types of solid tumors. Focusing on Copy Number Variation (CNV) array data, we have generated frequencies of deleted regions in HSA21 in four different tumor types from which DS patients have been reported to be protected. We describe three different regions of deletion pointing to a set of candidate genes that could explain the inverse comorbidity phenomenon between DS and solid tumors. In particular we found RCAN1 gene in Wilms tumors and the miR-99A, miR-125B2 and miR-LET7C in lung, breast and melanoma tumors as the main candidates for explaining the inverse comorbidity observed between solid tumors and DS.